Effects of direction change in running with and without the ball and performance level on metabolic demands in young basketball players. - Gaetano Altavilla (Asociación Española de Ciencias del Deporte, 2023)
Studying several types of running conditions with different tasks is useful to understand how metabolic demands change considering the complexity of the task performed (running with and without the ball). The hypothesis formulated is the following: the strength of the lower limbs may decrease more in the running with ball and between two groups (élite and sub-élite); while the energy expenditure should be different in four running conditions. The sample of subjects included twenty-four young male basketball players between 19±1 years old, divided in two groups (élite n=12 and sub-élite n=12). The aim of this study is to estimate the expenditure metabolic and the level of decreasing strength of the lower limb at different running conditions (two linear running and two shuttle running). The experimental approach required a portable Metabolimeter to assess the metabolic expenditures, Squat Jump (Optojump) to assess the strength of the lower limbs before and after each test. The T-test for independent sample was used and two-way repeated measures ANOVA to assess the significant differences for each running conditions. This study has showed a different metabolic expenditure between two groups: energy consumption is increased when running with the ball compared to when running without the ball and also when changing direction compared to linear running. The results could be useful to coaches to optimize the training load of young basketball players and to improve the motor learning.